Potential Drug Interactions between Recombinant Interleukin-2 and Direct Oral Anticoagulants: Indirect Evidence from In Vivo Animal Studies - Mahmoudpour, Seyed Hamidreza; Valerio, Luca; Douxfils, Jonathan; Mahan, Charles E.; Jankowski, Marius; Quitzau, Kurt; Konstantinides, Stavros V.; Barco, Stefano (Hämostaseologie, 2020)
Recombinant interleukin-2 (rIL-2) is indicated for metastatic renal cell carcinoma and melanoma. Over recent years low-dose rIL-2 has been studied for the treatment of autoimmune diseases and acute coronary syndrome because of its ability to expand and activate T regulatory (Treg) cells. However, several medical conditions potentially benefiting from rIL-2 administrations are characterized by an intrinsic prothrombotic risk, thus requiring concurrent anticoagulation. In our systematic review of the literature, we investigated the potential for drug interactions between oral anticoagulants and rIL-2 by assessing the influence of rIL-2 administration on transporters and cytochromes determining the pharmacokinetics of (direct) oral anticoagulants. We extracted data from 12 studies, consisting of 11 animal studies and one study in humans. Eight studies investigated the pharmacokinetics of P-glycoprotein (P-gp) substrates and reported that the intraperitoneal rIL-2 administration may inhibit intestinal P-gp. Four studies on hepatic cytochrome P450 yielded conflicting results. The only human study included in this systematic review concluded that rIL-2 suppresses the hepatic cytochrome P450, but only if given at higher doses. Based on the results from animal studies, the co-administration of rIL-2 and dabigatran etexilate, a substrate of intestinal P-gp, may lead to higher dabigatran plasma concentrations and bioavailability. Human studies should confirm whether this potential interaction is clinically relevant.
Keywords: interleukin-2; drug interaction; oral anticoagulants; systematic review